The Antibacterial and remineralizing effects of orthodontic adhesive modified by nano-chitosan loaded with calcium phosphate - Al-banaa, Lara Riyadh; Al-Khatib , Ali; Jabrail , Fawzi Habeeb (Brazilian Dental Science, 2025)
Objective: The objective of this study was to evaluate the remineralizing and antibacterial effects of orthodontic adhesive modified with nano-chitosan loaded with calcium phosphate, and to investigate the adhesive’s physical and chemical properties. Material and Methods: Transbond™ XT adhesive primer was modified by nano-chitosan loaded with calcium phosphate, this study compared three groups: Control primer without any additive, 5% and 10% nano-chitosan/ calcium phosphate primer in terms of Fourier Transform Infrared Spectrometer, Shear Bond Strength, Degree of monomer Conversion, Contact Angle measurement, Antibacterial properties against Streptococcus mutans and Lactobacillus acidophilus, and Field Emission Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy to examine remineralization of the demineralized enamel. Statistical Analysis used to compare the results using descriptive statistics, one-way ANOVA, and Tukey’s post hoc test. Statistical significance was set at P